A case of recurrent focal segmental glomerulosclerosis after kidney transplantation associated with variant conversion in the Columbia classification. (July 2015) - Unagami, Kohei; Kawanishi, Kunio; Shimizu, Tomokazu; Kanzawa, Taichi; Toki, Daisuke; Okumi, Masayoshi; Omoto, Kazuya; Horita, Shigeru; Koike, Junki; Honda, Kazuho; Nagashima, Yoji; Ishida, Hideki; et al.
Abstract: Focal segmental glomerulosclerosis commonly recurs following kidney transplantation. A 33‐year‐old man underwent living donor kidney transplantation. Proteinuria appeared two months after transplantation, and an episode biopsy on postoperative day 66 revealed recurrent focal segmental glomerulosclerosis lesions of the cellular variant by Columbia classification. We reviewed the native kidney biopsy and confirmed collapsing variant focal segmental glomerulosclerosis. Plasma exchange therapy was performed, and his proteinuria temporarily resolved. A second allograft biopsy performed on postoperative day 200 showed no evidence of focal segmental glomerurosclerosis. He experienced incomplete remission with a proteinuria of 0.5 g/day during the subsequent three years until his urinary protein level rose to 1.3 g/day. A third biopsy performed on postoperative day 1248 showed focal segmental glomerulosclerosis cellular variant lesions. Plasma exchange was resumed in combination with additional rituximab, but his proteinuria persisted. Intermittent plasma exchange was performed 42 times in total. However, his proteinuria continued, and his renal function gradually worsened. A fourth biopsy performed on postoperative day 2540 showed focal segmental glomerulosclerosis collapsing variant lesions with severe interstitial fibrosis and tubular atrophy. He ultimately required hemodialysis seven years after transplantation. Intensive therapy with long‐term intermittent plasma exchange and rituximab suppressed proteinuria and preserved graft function for seven years, at which time graft failure occurred. We here present the clinical course and histological findings from consecutive allograft biopsies.